The Student Worksheet Based on PBL Model to Develop Critical Thinking Skills in Phase A: Lembar Kerja Siswa Berbasis Model PBL untuk Mengembangkan Keterampilan Berpikir Kritis Tahap A - Fatkhur Rohman; Jody Setya Hermawan; Mia Azzahra; Handoko; Yoga Fernando Rizqi (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2024)
Mathematics is a subject that uses critical thinking skills in logical reasoning. This research was conducted on grade II students of SDN 1 Sukaraja, control class 24 students and experimental class 27 students. This research and development (R&D) study adopted the 4D model and reached only the third stage (define, design, develop). The product that was developed is a student worksheet that is based on the Problem-Based Learning (PBL) model. The goal is to train students' critical thinking skills. The developed student worksheet based on PBL model is proven to be